Aberrarone: A Gorgonian-Derived Diterpene from Pseudopterogorgia elisabethae - Rodríguez, Ileana I. (2009)
[Image: see text] A marine metabolite based on a previously undescribed carbon skeleton, aberrarone (1), is reported as a natural product from the Caribbean sea whip, Pseudopterogorgia elisabethae. The molecular structure of the crystalline metabolite was established by spectral analysis and subsequently confirmed by X-ray crystallographic analysis. Aberrarone shows in vitro antimalarial activity against a chloroquine-resistant strain of the protozoan parasite Plasmodium falciparum.